Courageous Leadership Needed to Create and Sustain Sexual Safety in Correctional Organizations. (June 2015) - Townsend, Cherie
Female staff members are overrepresented among perpetrators of staff sexual misconduct in prisons, jails, and juvenile facilities. That is the basic message of Allen Beck's thought-provoking article. This commentary provides a practitioner's perspective of his study and highlights the need for courageous leadership in preventing and responding to female staff sexual misconduct. The author considers the implications of the study's results for systems change and correctional organizations. While it is critical to acknowledge Dr. Beck's conclusions and to insure accountability for any staff engaging in sexual misconduct, the author emphasizes the need to also prevent this misconduct through leadership and healthy organizational cultures. Recommendations for further research and improved correctional practice are provided by the author.